Semantic Web Service Discovery Framework using Multi-Agents System And NLP Techniques - Essayah, A.; Youssfi, M.; Illoussamen, E.; Mansouri, K; Qbadou, M. (Transactions on Engineering and Computing Sciences, 2017)
As a consequently increase amount of web services available on the web, automatic discovery presents a great challenge, in order to satisfy this requirement, semantic discovery approaches based on ontologies have been developed. However, end-users do not have knowledge about semantic web languages to express their requirements. In this paper, we propose an automatic discovery framework based on multi-agent systems and natural language processing techniques to match a user request. The framework allows semantic matching through a set of semantic web services in order to enhance the accuracy of the discovery pattern, and to find a relevant match to the user request composed of keywords written in natural language. The use of multi-agent systems provide us the possibility to decrease the run-time by parallelizing simultaneous tasks, also, to implement various natural language processing techniques and matchmaking algorithms, and finally, they allow us to measure the users satisfaction through their behaviors dashboard analyze.